THE ORIGIN OF DOLOMITE IN EARLY CAMBRIANCARBONATES OF YORKE PENINSULA, WESTERN MARGIN OF STANSBURY BASIN, SOUTH AUSTRALIA - Maximon Shah Arifin (Testing Center for Oil and Gas LEMIGAS, 2002)
The Early Cambrian carbonate sequence in Yorke Peninsula consists of tidal flat lithologies in the lower part (Kulpara Fomation) and lagoonal lithologies with sporadic bioherms (Koolywurtie Member) in the upper part. Dolomitization have been recorded in those carbonates mainly of replacive nature, only small amounts are void-fill cement. Petrographic and stable isotopic analysis have supported the conclusion that dolomitization of the Early Cambrian carbonates in Yorke Peninsula was an ongoing process by hypersaline water followed by a mayor episode of recrystallization during shallow burial diagenesis, where enormous quantity of magnesium required for regional dolomitization is supplied by sea water. The geochemical and tectural modification of the dolomites are the result of a later stage recrystallization event, in shallow burial diagenetic environment by surfacederived meteoric 1 water.